The scandal of miscegenation: Miguel Gutiérrez rewrites Inca Garcilaso (Revista de Crítica Literaria Latinoamericana, 2017)
This article develops a reading of Peruvian Miguel Guitérrez's Poderes secretos (1995). Gutierrez's fiction proposes a deliberately absurd conspiracy theory that links Peruvian mestizaje, the national icon Inca Garcilaso de la Vega, a supposed secret academic cult, and a nefarious Jesuit plot from the colonial period. Gutiérrez places Inca Garcilaso at the heart of the conspiracy, and the novelists re-writes the biography of the famous mestizo historian, converting him into a plagiarist and the victim of a Jesuit plot whose consequences are still felt in modem times. In my analysis I investigate how Gutiérrez mobilizes the power of speculation and literary genre in order to open an unprecedented and unexpected reflection on Andean historiography and the elusive concept of mestizaje.
Keywords: miscegenation; conspiracy theory; Miguel Gutiérrez; Inca Garcilaso